(3GdeGdjI GdOhdjI (B:s (3eONd fXQj (B/s - (3QhGfj, HhMaUs ((3GdLRGFQ(B: s (3OGQ CLjGd GdQbej (B, s, 2023)
(3JWhQ GdfXGe GdeGdj GdOhdj YHQ GdRef, HOkAG ef fXGe GdUQa GdKGHJ Edi fXGe HQjJhf hhOR Ke Edi GdfXGe GdMGdj GdbGFe Ydi GdJYhje GdMQ Ch GdoeOGQ(B.(3, jTed GdfXGe GdeGdj GdOhdj GdeDSSGJ hGdCShGb GdeGdjI GdYGdejI, eKd UfOhb GdfbO GdOhdj hGdHfc GdOhdj hCShGb GdYedGJ hGdSfOGJ GdYGdejI, SLd ddeYGedGJ GdGbJUGOjI Hjf OhdI hHbjI Ohd GdYGde NdGd aJQI RefjI eMOOI, jYO ejRGf GdeOahYGJ eUOQG ZfjG HGdeYdheGJ GdeJYdbI HCOGA GdGbJUGOGJ Ydi GdeSJhi GdOhdj, hjJjM dUfGY GdbQGQ EecGfjI Gdhbha Ydi GdbOQI GdJfGaSjI dGbJUGOGJ (B... (3, SjGSI GdUQa GdCLfHj gj eLehYI GdELQGAGJ GdJj JJNPgG GdOhdI ddJCKjQ aj SYQ UQa YedJgG ebGHd GdYedGJ GdCLfHjI GdCNQi(B. (3h JTed SjGSGJ GdUQa GdKGHJ, hGdUQa GdoeOGQ, hGdJYhje GdMQ(B.(3, hPcQ dfG MQcI GdCehGd Hjf GdOhd, hJTed GdGSJKeGQGJ GdCLfHjI GdeHGTQI, hGdGSJKeGQGJ aj GdCSge hGdSfOGJ, hGdbQhV hGdeYhfGJ(B.(3, h JDKQ aj CSYGQ GdUQa hCSYGQ GdaGFOI hGdfeh GdGbJUGOj, (B. (3OQGSI hJMdjd GdCShGb GdeGdjI GdYGdejI, eKd CShGb GdYedGJ hCShGb GdCSge hGdSfOGJ, HgOa age GdeNGWQ hGdaQU GdGSJKeGQjI(B.(3hHYOg PcQ dfG GdJUfja GdGFJeGfj hGdJSjjQ GdeGdj GdOhdj gh EOGQI GdTDhf GdeGdjI ddTQcGJ GdJj JYed Ydi eSJhi Ohdj, HeG aj Pdc EOGQI GdeNGWQ GdeJYdbI HCSYGQ GdUQa hCSYGQ GdaGFOI(B. (3GdUjQaI GdOhdjI(B: (3h JbOje GdNOeGJ GdeUQajI ddYedGA GdPjf jYedhf Ydi eSJhi Ohdj, hJTed aJM GdMSGHGJ HGdYedGJ GdCLfHjI, hJMhjd GdCehGd, hJehjd GdJLGQI GdOhdjI(B. (3cPdc GdCReGJ GdeGdjI(B: (3JMdjd CSHGH hJOGYjGJ GdCReGJ GdeGdjI GdYGdejI, eKd GdCReI GdeGdjI GdYGdejI (B2008. (3GdJbdHGJ aj CSYGQ GdUQa(B: (3OQGSI CSHGH hfJGFL GdJbdHGJ aj CSYGQ GdUQa hJCKjQgG Ydi GdTQcGJ hGdGbJUGO GdYGdej(B. (3GdOjhf GdSjGOjI(B: (3JMdjd eTcdI GdOjhf GdSjGOjI hJCKjQgG Ydi GdOhd hGdGbJUGO GdYGdej(B. (3GdJcGed GdeGdj(B: (3OQGSI JWhQ GdJcGed GdeGdj Hjf GdOhd hJCKjQg Ydi GdCShGb GdeGdjI(B. s
(3eQGLY U(B.169-176s
Keywords: (3GdHhQUGJs; (3GdeMGSHI GdJMdjdjIs